Simulation on Gas Injection Refining Process with Mechanical Stirring - Liu Yan; Shao Pin; Zhao Hongliang; Zhang Junhua; Zhang Ting’an (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Basing on the new method of in-situ desulfurization with gas injection and mechanical stirring, the effect of bubble dispersion and disintegration of three type impellers are numerically simulated by commercial CFD software Ansys Fluent 12.0. Numerical simulations of three-dimensional multiphase turbulence in gas injection and mechanical stirring are performed by adopting unsteady SM method coupled with Eulerian multiphase model and two-phase turbulence model. The information of gas-liquid fluid flow, velocity, turbulent kinetic energy and the power consumption are investigated and the results show that the SSB impeller can make bubbles get best dispersion and disintegration，and its power consumption is lower than VB impeller. The disk on the impeller blades can weaken the swirl flow in the upper zone of the impeller. Therefore, the bubble residence time is extended, and the bubble dispersing zone is also increased. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1659